PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP MOTIVASI BELAJAR IPAS SISWA KELAS V SD NEGERI 128 PALEMBANG - Clarisha, Abel Dwie; Nur Syafarudin; Melinda Puspita Sari Jaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on the learning motivation of Grade V students in IPAS (Natural and Social Sciences) at SD Negeri 128 Palembang. This research uses a pre-experimental quantitative design with a one-group pretest-posttest design. The sample consisted of 31 students from class VA using purposive sampling technique. Data were collected using a learning motivation questionnaire consisting of 16 statements based on six indicators adapted from Sardiman (2014). Data analysis included normality testing (Shapiro-Wilk), homogeneity testing (Levene), and hypothesis testing using the paired sample t-test through SPSS 26. The normality test showed that both pretest (Sig. 0.173) and posttest (Sig. 0.082) data were normally distributed. The homogeneity test yielded Sig. 0.805, confirming that the data were homogeneous. The hypothesis test produced a t-count of -5.040 with Sig. (2-tailed) of 0.000, indicating that Ha was accepted and Ho was rejected. The mean pretest score was 59.32 (moderate category) and increased to 70.65 (high category) after treatment, a difference of 11.33 points. It is concluded that the Problem Based Learning model has a significant positive effect on the learning motivation of Grade V IPAS students at SD Negeri 128 Palembang.